2020
DOI: 10.33508/rima.v3i1.2746
|View full text |Cite
|
Sign up to set email alerts
|

Experiential Marketing and Experiental Value, How Does It Impact on Consumer Repurchase Intentions

Abstract: Today's competition is very intens, with many restaurants, cafes and food court popping up so that competition arises from the side of sellers and consumers. Today's consumers are more likely to get bored so quickly that they will use all existing facilities such as information technology to get information about what they want to know. Marketers must have a positive strategy in experiential marketing to create a good experience for consumers. This study aims to determine the effect of experiential marketing o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…With five comfortable senses will make consumers satisfied with our service. The success of MSMEs is also seen in terms of relationships between employees and consumers as targets (Yanto, Lindawati, and ... 2020). What is now a necessity is also for MSME businesses to continue to adjust.…”
Section: Resultsmentioning
confidence: 99%
“…With five comfortable senses will make consumers satisfied with our service. The success of MSMEs is also seen in terms of relationships between employees and consumers as targets (Yanto, Lindawati, and ... 2020). What is now a necessity is also for MSME businesses to continue to adjust.…”
Section: Resultsmentioning
confidence: 99%
“…Based on research conducted by (Yanto, Lindawati, & Pradana, 2020) found that the value of experience for consumers has a positive effect on intention to repurchase. When promoting, tutoring agency must also show the results of students who have succeeded, and provide a free experience of the learning process that is packaged in an attractive and professional manner.…”
Section: Experiencementioning
confidence: 99%
“…Customers have the ability to distinguish each product and service from different tourism objects since customers directly feel and experience the products or services given. The research which is conducted by Yanto et al (2020) showed results which mention that experiential marketing produces a positive and significant effect on repurchase at the Pasa Rami restaurant in Surabaya. The results of Sheng-HshiungTsaur, et al, (2007) research conducted at the Taipei Zoo, showed that experiential marketing gives a positive effect on emotions.…”
Section: Introductionmentioning
confidence: 99%